From Discontinuation to Commitment: A Participatory Model for Contraceptive Adherence - Sariati, Yuseva (LPPM Universitas Prima Nusantara Bukittinggi, 2026)
Background: Contraceptive discontinuation remains a critical challenge in reproductive health programs, threatening program sustainability and maternal health outcomes. Transforming patterns from discontinuation to sustained commitment requires innovative health promotion models that address multi-dimensional factors influencing contraceptive behavior. Understanding the pathway from discontinuation to continuity is essential for designing effective, context-specific interventions. Purpose: This study aimed to design a comprehensive health promotion model that transforms contraceptive discontinuation patterns into sustained commitment among acceptors in Malang Regency, Indonesia, utilizing Health Belief Model and Social Cognitive Theory as theoretical foundations Methods: An exploratory qualitative study using Grounded Theory methodology was conducted through Focus Group Discussions (FGDs) involving key stakeholders including heads of Population and Family Planning Department, health center directors, midwives, Family Planning Field Officers (PLKB), and community health workers in Malang Regency. Data analysis followed the three-stage Grounded Theory coding process: open coding, axial coding, and selective coding. Results The designed health promotion model encompasses five interconnected dimensions grounded in Health Belief Model and Social Cognitive Theory: Individual Factors (knowledge, attitudes, self-efficacy), Environmental Factors (social support, healthcare accessibility), Behavioral Factors (observational learning, reinforcement), Perceptions (perceived risks, benefits, barriers), and Sustained Participation in Contraceptive Services. The transformation pathway